A new study of multi-phase mass and heat transfer in natural gas hydrate reservoir with an embedded discrete fracture model - Cui, Yudong; Teng, Bailu; Luo, Wanjing; Lu, Cheng; Zhou, Yingfang (Frontiers in Earth Science, 2023)
Studies of the hydrate cores have shown that natural fractures can be frequently observed in hydrate reservoirs, resulting in a fracture-filled hydrate. Therefore, it is highly necessary for industries to predict the gas well productivity of fracture-filled hydrate reservoirs. In this work, an embedded discrete fracture model is applied to characterize the natural fractures of fracture-filled gas-hydrate reservoirs. The non-linear mass and energy conservation equations which are discretized with the finite-difference method are solved by the fully implicit approach, and the proposed model is justified by a commercial simulator. On the basis of the proposed model, we investigate the influences of natural fractures, fracture conductivity, and hydrate dissociation rate on the gas well productivity and the distributions of pressure, temperature, and hydrate saturation. The simulation results show that hydraulic and natural fractures exert significant impacts on the gas well productivity of the fracture-filled hydrate reservoirs, and the cumulative gas production is increased by 45.6% due to the existence of the connected natural fractures. The connected natural fractures can impose a more important influence on the gas well productivity than the unconnected natural fractures. The cumulative gas production is increased by 6.48% as Nnf is increased from 2 to 50, whereas the increase is 43.38% as Nf_con is increased from 0 to 4. In addition, A higher hydraulic fracture conductivity can be more favorable than a higher natural fracture conductivity for improving the gas well productivity, and a higher hydrate dissociation rate can lead to a lower temperature along fractures due to a more noticeable reduction of solid hydrate. This study provides a theoretical basis for developing fracture-filled hydrate reservoirs efficiently in the future.